Long-term use of benzodiazepines in chronic insomnia: a European perspective - Soyka, Michael; Wild, Imane; Caulet, Bérangère; Leontiou, Chrysoula; Lugoboni, Fabio; Hajak, Göran (Frontiers in Psychiatry, 2023)
Chronic insomnia occurs in ~10% of the general population and has numerous negative health effects. The recommended first line treatment of cognitive behavior therapy for insomnia is not widely available for patients in Europe, so pharmacotherapies such as benzodiazepine receptor agonist agents (benzodiazepines and Z-drugs) are commonly used. However, their use is only recommended for ≤4 weeks due to unproven long-term efficacy in treatment of chronic insomnia, and the risk of tolerance, and the potential for dependence and misuse. In Europe, recommendations limiting the use of benzodiazepines (lowest dose and shortest duration) in chronic insomnia are not always followed, likely due to the lack of approved effective alternative therapies. Here we present a recent pilot survey of the pharmacological treatment landscape in chronic insomnia in five European countries (France, Germany, Italy, Spain, and the UK) and physicians’ attitude towards treatment. The results suggest that benzodiazepines and Z-drugs are the most widely used treatments in chronic insomnia and are being used for longer than their recommended duration. Country variations in prescription rates were observed. Due to the known association between long-term benzodiazepine use and potential for developing dependence, further analysis of the literature was performed on the use and misuse of benzodiazepines. The results show that long-term use of benzodiazepines is associated with multiple consequences of treatment, including dependence, but also that previous use of benzodiazepines may increase the risk of opioid use disorder.